PROFESIONAL GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER SISWA - TINA DELIMA ULI MARPAUNG; Dorlan (JURNAL ILMIAH NUSANTARA, 2025)
Christian Religious Education (PAK) teachers have a very important role in the formation of character and faith of students, as well as in creating a generation with Christ-like personalities. This study aims to examine the professionalism of PAK teachers, the characters that must be possessed, and the competencies needed in carrying out their duties as educators. PAK teachers must have in-depth knowledge of Christian teachings, and be able to emulate Jesus as the Great Teacher in everyday life and in carrying out teaching duties. Through a literature study approach, this study explores various relevant sources to understand the role and qualifications of professional PAK teachers. The results of the study show that a professional PAK teacher not only masters the teaching material, but also has the character of Christ, high discipline, and great responsibility in educating and guiding students. A good PAK teacher must be a role model in all aspects of life, prioritize love, integrity, and responsibility, and continue to develop themselves both academically and spiritually. Professionalism in Christian religious education involves a deep understanding of the Word of God, ongoing training, and a high commitment to the task of teaching. Therefore, becoming a professional PAK teacher not only requires educational qualifications and competencies, but also the readiness to be a loving guide for students, preparing them to face life with Christian faith, integrity, and wisdom.